DAMPAK INVESTASI SEKTOR PERTANIAN TERHADAP PEREKONOMIAN SUMATERA BARAT (ANALISIS INPUT - OUTPUT) - Joan Marta (Universitas Negeri Padang, 2013)
This study aims to: (i) analyze the role of agriculture sector to the economy of West Sumatra in the formation of the structure of demand and the structure of supply, consumption structure, the structure of investment, export and import structure, structure of gross added value, (ii) determine the forward linkage and backward linkages of agriculture sector in the province of West Sumatra, (iii) determine the sensitivity coefficient of the spread and the spread of agriculture in West Sumatra, (iv) determine the multiplier effect caused by the agricultural sector in the province of West Sumatra, and (v) analyze the impact of investment generated by the agricultural sector to the economy in the province of West Sumatra. The results showed the assumption that investment in the agricultural sub-sectors Rp100 billion will have an impact on the increase in output, income and employment are able to create a total output in all sectors of the economy of Rp131,736.99 billion, revenue of Rp21 682, 46 billion, and the employment of 5,343 people. Based on this analysis, the impact of the agricultural subsector investment to the formation of the largest output value is in the plantation subsector, while the formation of the largest income on livestock sub-sector.